2015
DOI: 10.1002/2015wr017498
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating advances in continental domain hydrologic modeling

Abstract: In the past, hydrologic modeling of surface water resources has mainly focused on simulating the hydrologic cycle at local to regional catchment modeling domains. There now exists a level of maturity among the catchment, global water security, and land surface modeling communities such that these communities are converging toward continental domain hydrologic models. This commentary, written from a catchment hydrology community perspective, provides a review of progress in each community toward this achievemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
121
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 105 publications
0
121
0
Order By: Relevance
“…This knowledge could be valuable when estimating parameter values for continental-scale hydrological models. Currently, there is an emerging need for parameter estimation also in ungauged basins from several modeling communities (Archfield et al, 2015). For instance, traditional catchment models have recently been applied on a pan-European scale, e.g., SWAT (Abbaspour et al, 2015) and HYPE .…”
Section: Hydrological Interpretation Of Classes Using Cartmentioning
confidence: 99%
“…This knowledge could be valuable when estimating parameter values for continental-scale hydrological models. Currently, there is an emerging need for parameter estimation also in ungauged basins from several modeling communities (Archfield et al, 2015). For instance, traditional catchment models have recently been applied on a pan-European scale, e.g., SWAT (Abbaspour et al, 2015) and HYPE .…”
Section: Hydrological Interpretation Of Classes Using Cartmentioning
confidence: 99%
“…estimates (Sood and Smathkin, 2015), their ability to reproduce discharge observations at basin scale and to address practical water management issues is still limited (Archfield et al, 2015;Hattermann et al, 2018). Inaccuracies in runoff estimation from GHMs and LSMs may be first attributed to the uncertainty in global satellite precipitation products (Tian and PetersLidard, 2010;Sperna Weiland et al, 2015), but several studies have shown considerable differences between model outputs even when using the same meteorological forcing, given the lack of knowledge about runoff generation processes and 30 deficiencies in parameter estimation (e.g., Haddeland et al, 2011;Gudmundsson et al, 2012;Zhou et al, 2012;Beck et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to inadequate forcing data, the quality of which "is paramount in hydrologic modeling efforts" (Archfield et al, 2015) and/or the lack of good reference streamflow data for calibration and evaluation. Both surely play a role and emphasize the need for incorporation of additional data sets so that calibration and evaluation of intermediate states in the hydrologic cycle are examined.…”
Section: Model Accuracymentioning
confidence: 99%
“…Archfield et al (2015) state that the performance of continental-domain hydrologic models is considerably constrained by inadequate model representation of dominant hydrologic processes. For example, the simplicity of the MWBM presents limitations on the representation of deeper groundwater reservoirs, gain-ing and losing stream reaches, simplistic AET, and the effects of surface processes (infiltration and overland flow) that need to be represented at finer time steps than monthly.…”
Section: Model Accuracymentioning
confidence: 99%